Analysis of Vocabulary Errors in Descriptive Texts Written by Junior High School Students - sahraini, Alfiana; Ilmiawan; Rizki Bima Putra, Muhammad; Fakira, Zakiatul; Nasiroh; Khomisah, Laela; Yuliani; Al Hadis, Ilham; Jufiyansyah (Papanda Publisher, 2025)
English plays a strategic role in education because it serves as a means of global communication and an instrument for improving the quality of human resources. However, in learning practice, students still face obstacles in writing skills, especially in mastering vocabulary in descriptive texts. This study aims to identify and analyze vocabulary errors made by junior high school students and explore the factors that cause them. The research method used was qualitative descriptive with 30 students from class VIII B MTs NW Suwangi as subjects. The research instruments were written tests, documentation, and brief interviews with students and teachers. The data were analyzed using error analysis procedures, including identification, classification, and interpretation. The results of the study show that there are four main categories of errors, namely pronoun misuse (58.3%), word form error (25%), misuse of words (12.5%), and redundancy/repetition (4.2%). The main factors causing errors include mother tongue transfer, limited vocabulary, and generalization of grammar rules. The conclusion of this study confirms that vocabulary errors are a natural part of second language acquisition, reflecting the development of students' interlanguage. Therefore, teachers need to implement error-based learning through contextual exercises, descriptive vocabulary reinforcement, and the provision of meaningful language input.